Intermodule Coupling Analysis of Huang-Lian-Jie-Du Decoction on Stroke - Wang, Pengqian; Dai, Li; Zhou, Weiwei; Meng, Jing; Zhang, Miao; Wu, Yin; Huo, Hairu; Xiong, Xingjiang; Sui, Feng (Frontiers in Pharmacology, 2019)
Huang-Lian-Jie-Du Decotion (HLJDD) is a “Fangji” made up of well-designed Chinese herb array and widely used to treat ischemic stroke. Here we aimed to investigate pharmacological mechanism by introducing an inter-module analysis to identify an overarching view of target profile and action mode of HLJDD. Stroke-related genes were obtained from OMIM (Online Mendelian Inheritance in Man). And the potential target proteins of HLJDD were identified according to TCMsp (Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform). The two sets of molecules related to stroke and HLJDD were respectively imported into STRING database to construct the stroke network and HLJDD network, which were dissected into modules through MCODE, respectively. We analyzed the inter-module connectivity by quantify “coupling score” (CS) between HLJDD-modules (H-modules) and stroke-modules (S-module) to explore the pharmacological acting pattern of HLJDD on stroke. A total of 267 stroke-related proteins and 15 S-modules, 335 HLJDD putative targeting proteins and 13 H-modules were identified, respectively. HLJDD directly targeted 28 proteins in stroke network, majority (16, 57.14%) of which were in S-module 1 and 4. According to the modular map based on inter-module CS analysis, H-module 1, 2, 8 densely connected with S-module 1, 3 and 4, to constitute a module-to-module bridgeness, and the enriched pathways of this bridgeness with top significance were TNF signaling pathway, HIF signaling pathway, PI3K-Akt signaling pathway. Furthermore, through this bridgeness, H-module 2 and 4 cooperatively work together to regulate mitochondrial apoptosis against the ischemia injury. Finally, the core protein in H-module 4 account for mitochondrial apoptosis was validated by in vivo experiment. This study has developed an integrative approach by inter-modular analysis for elucidating the “shotgun-like” pharmacological mechanism of HLJDD for stoke.